Analisis Faktor-Faktor Yang Mempengaruhi Penyerapan Tenaga Kerja di Provinsi Bali - Khresna Putra, Putu Bayu; Utama, Made Suyana; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 11, November 2016 (pp. 1168 - 1346), 2016)
Economic development is the economic growth that is accompanied by changes in other aspects of the economy such as the development of education, the development of labor skills, technological improvements, and an increase in the level of prosperity of society. The purpose of this study was to determine the effect of variable tourist arrivals, economic stability and foreign investment simultaneously and partially on employment in the province of Bali. In addition, research is also carried out to determine which variables are the dominant influence on employment in the province of Bali. This study used is secondary data collection methods of data in the form of a literature study. Data analysis technique used is multiple linear regression analysis. The results showed that tourist arrivals, economic stability and foreign investment simultaneous and partial have significant effect on the employment period 1994-2014. Variable tourist arrivals are variables the dominant influence on the employment period 1994-2014.
Keywords: tourist arrivals; economic stability; foreign investment; employment